2019
DOI: 10.3389/fonc.2019.01201
|View full text |Cite
|
Sign up to set email alerts
|

CPT1A/2-Mediated FAO Enhancement—A Metabolic Target in Radioresistant Breast Cancer

Abstract: Tumor cells, including cancer stem cells (CSCs) resistant to radio- and chemotherapy, must enhance metabolism to meet the extra energy demands to repair and survive such genotoxic conditions. However, such stress-induced adaptive metabolic alterations, especially in cancer cells that survive radiotherapy, remain unresolved. In this study, we found that CPT1 (Carnitine palmitoyl transferase I) and CPT2 (Carnitine palmitoyl transferase II), a pair of rate-limiting enzymes for mitochondrial fatty acid transportat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 54 publications
0
79
0
Order By: Relevance
“…Lee et al have demonstrated that c-myc and mitochondrial protein Mcl1 cooperate to activate OXPHOS in breast cancer CSCs, thereby promoting drug resistance and tumor formation [ 62 ]. FAO has also been shown to activate OXPHOS in CSCs by supplying acetyl-CoA in the TCA cycle [ 89 , 130 , 138 ]. Han et al demonstrated that carnitine palmitoyltransferase 1A and 2, which are FAO rate-limiting enzymes, enhance the tolerance to radiation of breast cancer cells by enhancing ATP production by FAO [ 138 ].…”
Section: Metabolism Of Cscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al have demonstrated that c-myc and mitochondrial protein Mcl1 cooperate to activate OXPHOS in breast cancer CSCs, thereby promoting drug resistance and tumor formation [ 62 ]. FAO has also been shown to activate OXPHOS in CSCs by supplying acetyl-CoA in the TCA cycle [ 89 , 130 , 138 ]. Han et al demonstrated that carnitine palmitoyltransferase 1A and 2, which are FAO rate-limiting enzymes, enhance the tolerance to radiation of breast cancer cells by enhancing ATP production by FAO [ 138 ].…”
Section: Metabolism Of Cscsmentioning
confidence: 99%
“…FAO has also been shown to activate OXPHOS in CSCs by supplying acetyl-CoA in the TCA cycle [ 89 , 130 , 138 ]. Han et al demonstrated that carnitine palmitoyltransferase 1A and 2, which are FAO rate-limiting enzymes, enhance the tolerance to radiation of breast cancer cells by enhancing ATP production by FAO [ 138 ]. Furthermore, Citrate, which is generated from FAO-derived acetyl-CoA, is oxidized to α-ketoglutarate or pyruvate in cytoplasm and produces cytosolic NADPH [ 83 ].…”
Section: Metabolism Of Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that mitochondrial activity, which is critical for T-cell function, can be augmented by blocking PD1 or CTLA4 signaling, which consequently overcomes T-cell exhaustion ( 44 ). PD1 has been shown to affect T cells by prompting metabolic reprogramming toward depressed glycolysis and increased FAO, as well as increasing the expression of carnitine palmitoyl transferase 1A (CPT1A), which promotes the FAO of endogenous lipids ( 48 ). On the other hand, CTLA4 acts on T cells by inhibiting glycolysis with no augmentation of FAO ( 49 ).…”
Section: Immune Checkpoint Inhibitors and Mitochondrial Metabolismmentioning
confidence: 99%
“…Increased expression or abnormal activity of key lipogenic enzymes such as fatty acid synthase (FASN) and acetyl coenzyme A (acetyl-CoA) carboxylase is often attributed to the high growth rate and lipogenic phenotype of tumor cells ( 76 – 80 ). Moreover, carnitine palmitoyl transferase (CPT) 1 and 2, which are rate-limiting enzymes involved in mitochondrial fatty acid transportation, play crucial roles in increasing fatty acid oxidation required for the cellular fuel demands of breast cancer cells ( 81 ). CPT1A/CPT2 were highly expressed in recurrent human breast cancers and are associated with poor prognosis.…”
Section: Lipid Metabolism With Lncrnamentioning
confidence: 99%